Gaya Kepemimpinan Lurah Pondok dalam Membina Karakter Santri untuk Meningkatkan Kedisiplinan Beribadah di Pondok Pesantren Hidayatul Mubtadiin Lampung Selatan - Helis Suryani; Taqwatul Ulyah; Endang Ekowati (Journal on Education, 2024)
The reason for this exploration is to decide the execution of the town head's authority style at the Hidayatul Mubtadiin Islamic All inclusive School. The authority style of the town head in fostering the personality of understudies to work on their discipline in love at the Hidayatul Mubtadiin Islamic Live-in School. At the Hidayatul Mubtadiin Islamic Boarding School, what are the outcomes of the development of male village heads in developing the character of male students to improve their worship discipline? This kind of exploration is subjective. A descriptive method is used in the research method. Information assortment methods use meetings, perception and documentation. Information investigation, including information decrease, information show and information legitimacy really looking at process. Research results show that: 1) The Town Head's Authority Style in Fostering the Personality of Santri to Further develop Love Discipline at the Hidayatul Mubtadiin Islamic Life experience School utilizes a Vote based authority style. ( 2) Popularity based initiative completed by the Pondok subdistrict head is a wide range of endeavors to foster understudies, putting forth attempts through management, addresses, guidance, inspiration, as well as discipline/sanctions. ( 3) supporting elements in fostering the personality of santri to work on the discipline of santri love: the capacity of the town head to teach the santri and direct direction from the town head and executives through address strategies, counsel, direction and course to the santri, the accessibility of offices. The hindering elements in fostering the personality of understudies: absence of mindfulness of understudies in the discipline of love and absence of discipline in separating their time.